2017
DOI: 10.1149/07801.0689ecst
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Performance of LSM with A-site Non-Stoichiometry under Cathodic Polarization

Abstract: The electrochemical performance of (La 0.8 Sr 0.2 ) x MnO 3 (x=1.0, 0.95, 0.9) electrodes with YSZ electrolyte has been investigated as a function of the A-site non-stoichiometry. The effect of cathodic bias on the electrode polarization resistance and the mechanism of oxygen reduction reaction have been studied. The passage of cathodic current leads to extensive impact to the LSM/YSZ interface microstructure and significantly enhances the electrochemical activity. LSM with different A-site nonstoichiometry al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In agreement with previous studies, the ORR for blank LSM at OCV is dominated by the electrochemical processes occurring at the electrode/electrolyte interface, [ 63–65 ] while under cathodic polarization, oxygen vacancies are formed in LSM due to the reduction of Mn 4+ to Mn 3+ , which highly enhances the electrochemical properties. [ 66,67 ] This phenomenon leads to a new reaction path involving the bulk of the LSM particles. [ 63 ] Once the bulk path is activated, the determining factor for the ORR is the extension contact between the LSM and the electrolyte, which is enhanced for the cells with active layers.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with previous studies, the ORR for blank LSM at OCV is dominated by the electrochemical processes occurring at the electrode/electrolyte interface, [ 63–65 ] while under cathodic polarization, oxygen vacancies are formed in LSM due to the reduction of Mn 4+ to Mn 3+ , which highly enhances the electrochemical properties. [ 66,67 ] This phenomenon leads to a new reaction path involving the bulk of the LSM particles. [ 63 ] Once the bulk path is activated, the determining factor for the ORR is the extension contact between the LSM and the electrolyte, which is enhanced for the cells with active layers.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the La:Sr molar ratio on the A-site is relatively unchanged and the A:B site molar ratio significantly decreases from 0.95:1 to 0.86:1. It is well known that 5% A-site deficiency in LSM significantly improves polarization resistance compared to an A:B site molar ratio of 1:1 21,22,30,32,33 ; however, several studies have shown that increasing the A-site deficiency beyond 5% shows little improvement and in some cases actually increases polarization resistance. 21,33 Therefore, it is unlikely that the improvement in the high frequency peak is due to an increase in A-site deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that 5% A-site deficiency in LSM significantly improves polarization resistance compared to an A:B site molar ratio of 1:1 21,22,30,32,33 ; however, several studies have shown that increasing the A-site deficiency beyond 5% shows little improvement and in some cases actually increases polarization resistance. 21,33 Therefore, it is unlikely that the improvement in the high frequency peak is due to an increase in A-site deficiency. Another possible explanation for the improvement in high frequency impedance is related to heterogeneous changes in the LSM La:Sr molar ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Already in the early stages of SOFC development at FZ Jülich, [28,29] an A‐site deficient LSM composition was selected, because in combination with the YSZ electrolyte this composition is less susceptible to the undesired formation of a La 2 Zr 2 O 7 interlayer during sintering of the LSM electrode layer at elevated temperatures (1250 to 1350 °C) [30–32] . Further segregation mitigation strategies include nanoparticle infiltration [33] and anode [34] and microstructure [35] design to suppress high oxygen partial pressure [36] and anodic polarization, [20] which have been proposed to drive this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Solid oxide cells (SOCs), including solid oxide fuel cells (SOFCs) and solid oxide electrolysis cells (SOECs) are becoming increasingly important due to their relatively high energy conversion elevated temperatures (1250 to 1350 °C). [30][31][32] Further segregation mitigation strategies include nanoparticle infiltration [33] and anode [34] and microstructure [35] design to suppress high oxygen partial pressure [36] and anodic polarization, [20] which have been proposed to drive this phenomenon. Even though these strategies have shown promising results, cation segregation, especially of Sr, continues to impact cell performance, as the absence of fundamental understanding on the atomistic level prevents its systematic control.…”
Section: Introductionmentioning
confidence: 99%